Managerial Compensation in Multidivision Firms - Alok, Shashwat; Gopalan, Radhakrishnan (Management Science, 2018)
Using hand-collected data on division manager (DM) pay contracts, we document that DM pay is related to the performance of both the DM’s division and the other divisions in the firm. There is substantial heterogeneity in DM pay for performance. DM pay for division performance is lower in industries with less informative accounting earnings. DM pay is more sensitive to other-division performance if the DM’s division is related to the rest of the firm, if the DM’s division has fewer growth opportunities, and if the DM’s division receives less capital from the rest of the firm. Consistent with optimal contracting view, DMs receive greater pay for other-division performance in better-governed firms. Overall, our evidence suggests that DM compensation is structured to account for the information and agency problems in multidivision firms. The Internet appendix is available at https://doi.org/10.1287/mnsc.2016.2672 . This paper was accepted by Amit Seru, finance.